Prevalence of carbapenemase-producing organisms at the Kidney Center of Rawalpindi (Pakistan) and evaluation of an advanced molecular microarray-based carbapenemase assay. (September 2018) - Braun, Sascha D; Jamil, Bushra; Syed, Muhammad A; Abbasi, Shahid A; Weiß, Daniel; Slickers, Peter; Monecke, Stefan; Engelmann, Ines; Ehricht, Ralf
Aim: A DNA microarray-based assay for the detection of antimicrobial resistance (AMR) genes was used to study carbapenemase-producing organisms at the Kidney Center of Rawalpindi, Pakistan.Methods: The evaluation of this assay was performed using 97 reference strains with confirmed AMR genes. Testing of 7857 clinical samples identified 425 Gram-negative bacteria out of which 82 appeared carbapenem resistant. These isolates were analyzed using VITEK-2 for phenotyping and the described AMR assay for genotyping.Results: The most prevalent carbapenemase gene was bla NDM and in 12 isolates we detected two carbapenemase genes (e.g., bla NDM/ bla OXA-48).Conclusion: Our prevalence data from Pakistan show that – as in other parts of the world – carbapenemase-producing organisms with different underlying resistance mechanisms are emerging, and this warrants intensified and constant surveillance.